The Effect of Environmental, Social, and Governance (ESG) Disclosures on Firm Value Measured by Tobin’s Q: Evidence from Hospital and Pharmaceutical Sectors in Indonesia (2021–2024) - Yanuar Ramadhan; Ferry Hendro Basuki (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: ESG disclosure has become increasingly important, particularly in Indonesia’s healthcare sector, where hospitals and pharmaceutical companies must balance profit with environmental and social accountability amid growing regulatory and stakeholder demands. Objective: This study explores the link between ESG integration and healthcare company valuation, assessing firm value through Tobin’s Q, which compares a business’s market price to its recorded assets. Methods: Using EViews for analysis, this quantitative study applied multiple linear regression to evaluate how ESG factors influenced firm value between 2021 and 2024, drawing from public annual and sustainability reports. Results: The study indicates that a company’s value is partially driven by its social and environmental performance. Effective green practices and community engagement tend to foster more favorable perceptions from the investment community. However, since governance does not significantly affect valuation, investors appear to focus more on how firms treat the environment and society rather than on specific administrative or board-level policies. Conclusion: Findings from this study support legitimacy theory, suggesting that healthcare businesses prioritize building trust with communities and investors to align with social expectations. This strategic alignment enhances market standing and results in higher corporate valuation.